Transnational democracy : political spaces and border crossings - Anderson, James, 1941- (Routledge, 2002)
A multidisciplinary array of experts explore the issues related to globalisation and democracy. They focus on federalism, multi-cultural societies, the European Union and potential agents for the democratisation of global institutions.
Keywords: Democracy.; World politics.; Citizenship.; Sovereignty.; International organization.; International relations.; Politique mondiale.; Souveraineté.; Organisation internationale.; Relations internationales.; sovereignty.; international relations.; POLITICAL SCIENCE -- Globalization.; Citizenship; Democracy; International organization; International relations; Sovereignty; World politics